SARS-CoV-2 Inactivation by Ozonated Water: A Preliminary Alternative for Environmental Disinfection - Martins, Ronaldo B.; Castro, Italo A.; Pontelli, Marjorie; Souza, Juliano P.; Lima, Thais M.; Melo, Stella Rezende; Siqueira, João Paulo Zen; Caetano, Maicon Henrique [UNESP]; Arruda, Eurico; de Almeida, Margarete Teresa Gottardo (Taylor & Francis, 2021)
The rapid spread of SARS-CoV-2 caused a global pandemic. Due to the lack of treatment and vaccines, safety strategies must be found to stop the virus dissemination. The objective of this study was to evaluate the virucidal activity of ozonated water, a powerful oxidizing agent, against SARS-CoV-2. A special faucet was the source of ozonated water at a low concentration (0.2–0.8 ppm). At this concentration, tests with SARS-Cov-2 in Vero CCL81 lineage showed two log10 reduction in virus infectivity upon 1 min exposure to ozonated water, in comparison to controls. It shows the potential as an efficient and rapid alternative for controlling viral spread in hospitals and other environments.
Keywords: COVID-19; disinfection; infection control; ozonated water; Ozone; SARS-CoV-2; virus inactivation